APPLICATION OF THE ION CHROMATOGRAPHY METHOD IN BIOTECHNOLOGY FOR THE JOINT DETERMINATION OF MONO- AND DISACHARIDES - Anastasiya Eremina; Marina Skorokhodova; Elena Budkevich; Roman Budkevich (Вестник Северо-Кавказского федерального университета)
Biotechnologicalprocesses in the processing of raw materials lead to the transformation of disaccharides into monosaccharides, which necessitate the identification of these components in one analysis. The article considers the possibility of direct detection ofcarbohydrates mixture using an electrochemical detector operating in a pulsed amperometric mode. A general scheme for preparation of a sample for various polydisperse colloidal systems containing mixtures of carbohydrates is proposed. The possibility of ion chromatography for analyzes of carbohydrate-containing food raw materials and products of enzymatic hydrolysis of dairy products was shown.